Verification of failure mechanisms and design philosophy for a bolt-anchored and fibre-reinforced shotcrete lining. (October 2020) - Sjölander, Andreas; Hellgren, Rikard; Malm, Richard; Ansell, Anders
Highlights: Numerical modelling of a bolt-anchored and fibre-reinforced shotcrete lining. Material models to study failure of shotcrete, bond and rock bolts. Verification of failure modes derived from experimental testing. Influence of individual failure mechanism on structural behaviour. Abstract: Falling or sliding of loose blocks is one of the most common failure modes in a rock tunnel. For tunnels in hard and jointed rock, fibre-reinforced shotcrete (sprayed concrete) in combination with rock bolts is one of the most commonly used supports to prevent such failures. The structural behaviour, and especially the failure, of this type of rock support, is complex and involves several failure mechanisms; such as cracking of the shotcrete and interface failure along the shotcrete-rock, bolt-grout and rock-grout interface. Therefore, rock supports are normally designed using analytical solutions based on the independent failure modes. However, these failure modes are derived based on experimental testing and the assumption that no interaction between the failure modes occur. This assumption has not been verified. Therefore, this paper presents a numerical model capable of simulating the failure of a bolt-anchored and fibre-reinforced shotcrete lining. The model includes bond failure between shotcrete and rock, cracking of the shotcrete and pull-out failure of rock bolts. The structural behaviour for each failure mode and the complete structure have been verified against experiments from the literature. This shows that the model is capable of simulating the different phases of failure, and show good agreement with results from full-scale experimental tests from the literature. Furthermore, results from the numerical simulation confirms that the design of the shotcrete lining can be based on individual failure mechanisms. Moreover, it was shown that a design based on the residual strength of the fibre-reinforced shotcrete is conservative compared to a design based on the bond strength.